2018
DOI: 10.1111/edt.12388
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about traumatic dental injuries in the permanent dentition: A survey of Lithuanian dentists

Abstract: Lithuanian general dentists have insufficient dental traumatology knowledge. Better knowledge was observed amongst younger dentists (≤50 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
58
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 30 publications
15
58
1
6
Order By: Relevance
“…The majority of respondents (61%) self‐reported having at least a good knowledge about dental traumatology. The present study results revealed that a higher self‐reported knowledge was associated with a higher level of competence on dental trauma treatment, which is in accordance with the literature …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The majority of respondents (61%) self‐reported having at least a good knowledge about dental traumatology. The present study results revealed that a higher self‐reported knowledge was associated with a higher level of competence on dental trauma treatment, which is in accordance with the literature …”
Section: Discussionsupporting
confidence: 93%
“…There has been a progressive increase in enrollment of Brazilian women in universities since the 1980s, and a predominance of female dentists can be observed from the late 1990s to the present day, which confirms that the feminization of dentistry is occurring . This was observed in the sample from the current study, and in previous studies …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations